THE UNITED NATIONS SECURITY COUNCIL RESOLUTION ON SANCTIONS TOWARDS INDIVIDUAL FROM THE PERSPECTIVE OF INTERNATIONAL LAW - Jessica Priscilla Suri (International Law Department, Faculty of Law Universitas Padjadjaran, 2019)
AbstractThe United Nations Security Council (SC) holds the primary responsibility to maintain international peace and security as stipulated in Article 24 of the United Nations Charter (UN Charter). The emergence of international terrorism as a threat to international peace and security encourages the SC to impose sanctions in the form of assets freeze, travel ban and arms embargo towards targeted individuals through the SC Resolutions on Taliban, Al-Qaida and the Islamic State of Iraq and the Levant (ISIL). However, the implementation of UN targeted sanctions towards individuals has been violating the targeted individual’s human rights to property, rights of movement, rights to privacy, honor and reputation, and also the rights to a fair trial. This article will explain about the legitimation of the SC Resolutions in imposing sanction towards an individual, and the obligation of UN member states towards the SC resolution that imposes sanctions against its citizen. The violations of human rights stemming from the implementation of SC Resolutions on sanction towards individuals indicate that the resolutions have been adopted beyond the limits of international law. Therefore this condition makes the resolutions lost its legitimacy under international law. In accordance with Article 25 and 103 of the UN Charter, all member states have an obligation to accept, carry on and give priority to the obligation originating from the SC Resolution including to implement the sanction measures towards individuals. Nevertheless, member states must accommodate and harmonize its obligations in respecting, protecting and fulfilling all the individuals’ rights who are targeted by the SC along with its obligation to the SC Resolutions. Keywords: Human Rights, Sanction towards Individuals, United Nations Security Council.AbstrakDewan Keamanan Perserikatan Bangsa-Bangsa (DK) memiliki tanggungjawab utama untuk menjaga perdamaian dan keamanan internasional berdasarkan Pasal 24 Piagam PBB. Munculnya terorisme internasional sebagai ancaman terhadap perdamaian dan keamanan internasional mendorong DK untuk menjatuhkan sanksi berupa pembekuan aset, pelarangan perjalanan serta embargo senjata kepada individu yang ditargetkan melalui rezim Resolusi Taliban, Al-Qaida dan Islamic State of Iraq and the Levant (ISIL). Dalam penerapannya penjatuhan sanksi tersebut menimbulkan pelanggaran Hak Asasi Manusia (HAM) yaitu hak terhadap properti, hak kebebasan berpindah, hak atas privasi, kehormatan dan reputasi serta hak atas proses pengadilan yang adil. Pelanggaran HAM tersebut memunculkan tujuan dilakukannya penulisan artikel ini yaitu untuk menunjukan mengenai legitimasi resolusi DK yang menjatuhkan sanksi kepada individu, serta memaparkan mengenai kewajiban negara anggota PBB terhadap resolusi DK yang menjatuhkan sanksi kepada warga negaranya. Pelanggaran HAM yang disebabkan oleh penerapan penjatuhan sanksi terhadap individu mengindikasikan bahwa resolusi yang mendasari penjatuhan sanksi tersebut diadopsi dengan melampaui batasan-batasan penjatuhan sanksi DK dan telah kehilangan legitimasinya menurut hukum internasional. Sehingga meskipun negara memiliki kewajiban berdasarkan Pasal 25 dan 103 Piagam PBB untuk tetap menerima, melaksanakan dan mengutamakan kewajibannya berdasarkan Resolusi DK yang menjatuhkan sanksi terhadap individu, negara tetap harus mengakomodir dan mengharmonisasikan kewajibannya dalam menghormati, melindungi dan memenuhi HAM individu yang dijatuhkan sanksi saat melaksanakan kewajibannya yang berasal dari Resolusi DK. Kata Kunci: Dewan Keamanan Perserikatan Bangsa-Bangsa, Hak Asasi Manusia, Sanksi terhadap Individu